The costs and benefits of formalization for firms: A mixed-methods study on Mozambique - Hanna Berkel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper is the first to use a panel dataset from the African continent to investigate the relationship between formalization and firm outcomes. Instead of applying a binary formality indicator, it constructs a conceptual framework that regards informality as a continuum consisting of four degrees. The quantitative data includes 516 manufacturing enterprises which are analysed through a matched double difference approach. Moreover, the study explores participant observation as well as semi-structured interviews with government officials, experts, and entrepreneurs to explain the quantitative results and to examine additional effects of formalization. It suggests that the most informal firms do not benefit from formalization due to their underlying conditions. Other, more formal enterprises benefit but there is scope for increasing the benefits and decreasing the costs of formalization. Further, an improvement of the costs and benefits is not enough: better institutions are needed.
Keywords: D21; L60; O12; O17; 330; informality; formalization; firms; manufacturing; Mozambique; mixed-methods